Linguistic Landscape around the Bringing-Up Process. Archaisms and Euphemisms as Language Enclaves - Kunicka, Małgorzata (INSTED: Interdisciplinary Studies in Education & Society, 2020)
The language determines human cognition, it enables to separate things in the world and to always consider any world cognition as an interpretation in language. The concepts and terms support processes of shaping stereotypes of thinking about the reality and are the reason for deforming the picture of the objective world in the users? consciousness. In the pedagogical lexical landscape there appear concept enclaves filled-in by words recognised as useless under the promoted educational ideology and by the terms that are driven away by more ?modern? ones and by those which were supplanted by their replacements not counterbalancing the meaning layer, but positively received by the doctrine?s supporters. The article shows this type of enclaves, where the indicator of belonging to the world outside them is to show a politically correct language serving the currently binding educational ideology.